ANALISIS PENDAPATAN USAHATANI KOPI DI DESA PURWEREJO TIMUR, KECAMATAN MODAYAG, KABUPATEN BOLAANG MONGONDOW TIMUR - Ronaldo Esayas Amisan; O. Esry H. Laoh; Gene H. M. Kapantow (Sam Ratulangi University, 2017)
This study aims to determine the income of coffee farming. The location of this research was East Purwerejo Village, Modayag Sub-district, East Bolaang Mongondow District. Data collection is done by taking primary data and secondary data. Primary data were obtained from farmers through a list of prepared questions, while secondary data were obtained from village offices. Sampling method used Simple Ramdom Sampling by taking samples of 20 farmers. Data collecting method used is descriptive analysis. The results of this study indicate that the existing coffee farming in Purwerejo Timur village has benefited and is feasible to cultivate due to higher income compared to expenditure cost incurred by farmers.